ANALISIS DAYA SAING KAKAO INDONESIA DI PASAR INTERNASIONAL - Napitupulu, Donal Arianto; Gabriel, Philip Yudha; Sirait, Rhutnalia; Prayoga, Ryan (Universitas Veteran Bangun Nusantara, 2024)
Cocoa is one of the major indonesian agricultural export product.cocoa international market has great potential regarding world’s conseption growth therefore indonesian is expected to the take adventage on exsisting opportunities . The aims of this study were to analyze the competitiveness of Indonesian cocoa beans and processed cocoa trade in the international market as well as the level of competition between cocoa exporting countries. By using Revealed Comparative Advantage (RCA) and Spearman Rank Correlation, it showed that Indonesia had a comparative advantage as an cocoa exporter on the international market, the highest for cocoa beans and the lowest for cocoa paste; Indonesia also had a significant correlation to exporting countries in cocoa beans’ market (Ghana) and cocoa paste’s market (Netherlands and Malaysia), the correlation suggests that there were high correlation between Indonesia and the exporting country in competing for market share. Keywords: cocoa, comparative advantage, international trade, competitiveness, market share, RCA